Gambaran Telur Soil Transmitted Helminth (STH) Pada Anak-anak Yang Terindikasi Stunting Menggunakan Metode Natif - Widyanti, Tuty; Rahmawati, Rahmawati; Anita, Anita; Fatmawati, Andi; Sudirman, Hirrnawati (Universitas PGRI Palembang, 2024)
Soil-transmitted Helminth (STH) worm eggs are a type of intestinal parasite that can cause infections in humans, especially children. This parasitic infection can cause stunting, which can have a negative impact on health. This study aims to determine the description of soil-transmitted helminth (STH) eggs in children with indications of stunting. This research was carried out using laboratory observations. The object of this research was to collect feces using a random sampling technique with a direct (native) method. Based on the research that has been carried out, of the 16 feces samples, 9 positive samples were found to have soil-transmitted helminth (STH) worm eggs consisting of 7 Ascaris lumbricoides egg samples, 2 Trichuris trichiura egg samples, and 7 negative samples. It follows that one possible cause of childhood stunting could be the egg infection caused by soil-transmitted helminth (STH) worms.